Influence of anneling condition on the structure and magnetic properties of NdFeB thin films - Luu, Tai Tuan; Than, Hien Duc; Ta, Khoa Van; Le, Tu Tuan (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts